1988
DOI: 10.1002/jcc.540090105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanics parameters for organosilicon compounds calculated from ab initio computations

Abstract: Molecular structures of 26 organosilicon compounds have been optimized using ab initio calculations at the 3-21G* (modified) level. From these optimized structures, the internal coordinates have been deformed and the variation of the total molecular energy has been studied. Parameters for stretching and bending deformations are reported herein. The bending potential for the Si-0-Si bond which has an unusual flexibility is also included. Nonbonding interactions are described in terms of steric and electrostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The average bond angle at the oxygen varies between 130 0 and 180 °C. This wide bond angle, as well as the balance of the electrostatic and dispersion interactions, provide another important difference between organosiloxanes and other organic compounds: the chain conformation of siloxanes consists of sequential bonds in alternating cis-trans conformation [2], while the most stable conformation of hydrocarbons, for example, is trans-trans. Such molecular differences are expected to have an impact on the physical and chemical properties of the corresponding substances.…”
Section: Physico-chemical Properties May Be Broadly Classified Into Tmentioning
confidence: 99%
“…The average bond angle at the oxygen varies between 130 0 and 180 °C. This wide bond angle, as well as the balance of the electrostatic and dispersion interactions, provide another important difference between organosiloxanes and other organic compounds: the chain conformation of siloxanes consists of sequential bonds in alternating cis-trans conformation [2], while the most stable conformation of hydrocarbons, for example, is trans-trans. Such molecular differences are expected to have an impact on the physical and chemical properties of the corresponding substances.…”
Section: Physico-chemical Properties May Be Broadly Classified Into Tmentioning
confidence: 99%
“…8,47 It has since been correctly pointed out that in disiloxane the barrier to conversion from conformation I to II is lower by rotation of the H 3 Si-groups, than inversion of the Si-O-Si angle. 7 However, considering the very low experimental and theoretical barriers, we would expect significant populations of linear or near-linear conformations at room temperature.…”
Section: Energetic Barrier To Linearizationmentioning
confidence: 99%
“…There are two possible C, conformations of disiloxane, the doubly staggered (I) and the doubly eclipsed (11), shown in Figure 1. On the basis of electron diffraction data, Almenningen et al' concluded that disiloxane has the C2, symmetry of conformation I. Disiloxane crystals exhibit a distorted C, structure similar to 1.…”
Section: Experimental Lhltamentioning
confidence: 99%